Evaluating cost benefits from a heat health warning system in Adelaide, South Australia. (23rd December 2021) - Williams, Susan; Nitschke, Monika; Wondmagegn, Berhanu Yazew; Tong, Michael; Xiang, Jianjun; Hansen, Alana; Nairn, John; Karnon, Jonathan; Bi, Peng
Abstract: Objective : To examine the cost benefits of a heat health warning system (HHWS) in South Australia. Methods : Information from key agencies was used to estimate the costs associated with the South Australian HHWS, including for three targeted public health interventions. Health cost savings were estimated based on previously reported HHWS‐attributable reductions in hospital and emergency department (ED) admissions and ambulance callouts. Results : The estimated cost for a one‐week activation of the HHWS was AU$593, 000. Activation costs compare favourably with the potential costs averted through HHWS‐attributable reductions in hospital admissions and ambulance callouts with an estimated benefit‐cost ratio of 2.0–3.3. Conclusions : On the basis of estimated cost benefit, the South Australian HHWS is a no‐regret public health response to heatwaves. Implications for public health : As global temperatures rise there are likely to be significant health impacts from more frequent and intense heatwaves. This study indicates that HHWSs incorporating targeted supports for vulnerable groups are likely to be cost‐effective public health interventions.